Intratumoral administration of CD1c (BDCA-1)+ and CD141 (BDCA-3)+ myeloid dendritic cells in combination with talimogene laherparepvec in immune checkpoint blockade refractory advanced melanoma patients: a phase I clinical trial - Bart Neyns; Angela Vasaturo; Julia Katharina Schwarze; Gil Awada; Ramses Forsyth; Jens Tijtgat; Louise Cras; Christopher Bagnall; Inès Dufait; Sandra Tuyaerts; Ivan Van Riet (Journal for ImmunoTherapy of Cancer, 2022)
Background Intratumoral (IT) myeloid dendritic cells (myDCs) play a pivotal role in initiating antitumor immune responses and relicensing of anti-tumor cytotoxic T lymphocytes within the tumor microenvironment. Talimogene laherparepvec (T-VEC) induces immunogenic cell death, thereby providing maturation signals and enhancing the release of tumor antigens that can be captured and processed by CD1c (BDCA-1)+ / CD141 (BDCA-3)+ myDCs, in order to reinvigorate the cancer-immunity cycle.Methods In this phase I trial, patients with advanced melanoma who failed standard therapy were eligible for IT injections of ≥1 non-visceral metastases with T-VEC on day 1 followed by IT injection of CD1c (BDCA-1)+ myDCs +/- CD141 (BDCA-3)+ myDCs on day 2. T-VEC injections were repeated on day 21 and every 14 days thereafter. The number of IT administered CD1c (BDCA-1)+ myDCs was escalated from 0.5×106, to 1×106, to a maximum of 10×106 cells in three sequential cohorts. In cohort 4, all isolated CD1c (BDCA-1)+ / CD141 (BDCA-3)+ myDCs were used for IT injection. Primary objectives were safety and feasibility. Repetitive biopsies of treated lesions were performed.Results In total, 13 patients were enrolled (cohort 1 n=2; cohort 2 n=2; cohort 3 n=3; cohort 4 n=6). Patients received a median of 6 (range 3–8) T-VEC injections. The treatment was safe with most frequent adverse events being fatigue (n=11 (85%)), fever (n=8 (62%)), and chills/influenza-like symptoms (n=6 (46%)). Nine (69%) and four patients (31%), respectively, experienced pain or redness at the injection-site. Clinical responses were documented in injected and non-injected lesions. Two patients (cohort 3) who previously progressed on anti-PD-1 therapy (and one patient also on anti-CTLA-4 therapy) developed a durable, pathologically confirmed complete response that is ongoing at 33 and 35 months following initiation of study treatment. One additional patient treated (cohort 4) had an unconfirmed partial response as best response; two additional patients had a mixed response (with durable complete responses of some injected and non-injected lesions). On-treatment biopsies revealed a strong infiltration by inflammatory cells in regressing lesions.Conclusions IT coinjection of autologous CD1c (BDCA-1)+ +/- CD141 (BDCA-3)+ myDCs with T-VEC is feasible, tolerable and resulted in encouraging early signs of antitumor activity in immune checkpoint inhibitor-refractory melanoma patients.Trial registration number NCT03747744.